2013
DOI: 10.4187/respcare.01968
|View full text |Cite
|
Sign up to set email alerts
|

Disease Management Programs for Patients With Asthma in Germany: A Longitudinal Population-Based Study

Abstract: BACKGROUND:The primary aim of the disease management program (DMP) for patients with asthma is to improve health outcomes and to reduce costs. Five years after its introduction in Germany, no consensus has yet been reached as to whether DMP has been effective in reaching these goals. OBJECTIVE: To evaluate the DMP for asthma in Bavaria using routinely collected subject medical records. METHODS: A longitudinal population-based study encompassing over 100,000 DMP participants between 2006 (when the program began… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 20 publications
1
13
1
Order By: Relevance
“…This may reflect the debate about the extent of the benefits of written management plans [35] since these benefits were first presented in 2004 [36]. The proportion of physicians employing written plans in Germany recorded in our study (37%) is lower than published data from the German Disease Management Programme (DMP) evaluation would suggest [37]. Another study reported this discrepancy in use of written plans between German patients enrolled in the DMP and those not enrolled [38], demonstrating both the need to assess a representative population when calculating overall population estimates and the potential benefit of enrollment on such a structured programme.…”
Section: Discussioncontrasting
confidence: 63%
“…This may reflect the debate about the extent of the benefits of written management plans [35] since these benefits were first presented in 2004 [36]. The proportion of physicians employing written plans in Germany recorded in our study (37%) is lower than published data from the German Disease Management Programme (DMP) evaluation would suggest [37]. Another study reported this discrepancy in use of written plans between German patients enrolled in the DMP and those not enrolled [38], demonstrating both the need to assess a representative population when calculating overall population estimates and the potential benefit of enrollment on such a structured programme.…”
Section: Discussioncontrasting
confidence: 63%
“…Promising results have been shown by targeting new adherence interventions, like speech recognition telephone calls, or by other e‐health tools, or disease management programmes . Another opportunity to improve adherence is to enhance the promising pharmacist‐led targeted interventions in patients with asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Recommendations for the use of specific support programs for patients with COPD are based on experience with other chronic diseases such as diabetes [20], coronary artery disease [21], and asthma [22]. Studies investigating the utility of such programs for COPD reported heterogeneous conclusions, and meta-analyses have argued that more studies are needed [23, 24].…”
Section: Discussionmentioning
confidence: 99%